Handwritten English Word Recognition Based on Convolutional Neural Networks - Aiquan Yuan; Gang Bai; Po Yang; Yanni Guo; Xinting Zhao (2012 International Conference on Frontiers in Handwriting Recognition, 2012)
This paper presents a novel segmentation-based and lexicon-driven handwritten English recognition systems. For the segmentation, a modified online segmentation method based on rules are applied. Then, convolutional neural networks are introduced for offline character recognition. Experiments are evaluated on UNIPEN lowercase data sets, with the word recognition rate of 92.20%.